Mother tongue other tongue: nine years of creative multilingualism in practice. (2nd January 2022) - Edwards, Jess; Mohammed, Noor; Nunn, Caitlin; Gray, Paul
ABSTRACT: This article assesses the impact over nine years of the Mother Tongue Other Tongue multilingual schools' poetry competition led by Carol Ann Duffy from Manchester Metropolitan University, in which over 35, 000 pupils from 77 schools have participated to date. It reviews evidence from a 2019 evaluation of the project and from a project anthology compiling several years of winning entries. The evidence suggests that the project is achieving its expected outcomes in increasing the self-confidence of bilingual and multilingual pupils, enhancing inclusivity and cultural exchange in the classroom and fostering dialogue and co-creation between children and their families. This article sets these outcomes within the context of research on urban multilingualism in Manchester, poetry in the UK National Curriculum, and creative multilingualism in English education, and seeks to extend the case made by previous articles in this journal for the educational value of multilingual creative writing.